The Virtual Screening of Flavonoid Derivatives on Progesterone, Estrogen, and HER-2 Receptor for Breast Cancer Treatment Candidate - Septian, Ade Dwi; Wardani, Gatut Ari; Mardianingrum, Richa; Ruswanto, Ruswanto (Syarif Hidayatullah State Islamic University, 2023)
Cancer is defined as a disease caused by progressive and abnormal cell proliferation in the body. This condition is caused by deoxyribonucleic acid (DNA) changes, which causes cells to lose their normal function. The aim of this study is to find that flavonoid compounds have a more stable interaction than tamoxifen as anti-cancer candidates. Research has been conducted in silico with molecular docking (AutodockTools-1.5.7) and molecular dynamics of 200 flavonoid compounds. Furthermore, pharmacokinetic parameters, toxicity, and the application of the Lipinski Rule of Five were investigated. Based on molecular docking results, the compounds eriocotrin, glabrol, kaempferitrin, linarin, and narirutin have more stable interactions with lower binding energy (∆G) than tamoxifen. From the results of molecular docking, molecular dynamics, and pharmacokinetic studies, it is predicted that the kaempferitrin compound can be used as an anti-cancer candidate and does not cause toxicity through further research.